DEVELOPING TEACHING AIDS BASED ON WINGEOM SOFTWARE USING TUMBUR SCULPTURE ON LINE AND ANGLE MATERIALS AT CLASS VII OF SMP - Dasmasela, Jakobus; Laurens, Theresia; Ayal, Carolina Selfisina (Jurnal Magister Pendidikan Matematika (JUMADIKA), 2024)
Mathematics is considered difficult because it has several characteristics, one of which is the study of abstract objects which causes most students to experience difficulties. The results of interviews and initial observations at one of the junior high schools in Saumlaki found that students' ability to solve mathematical problems was very low as evidenced by students' ability tests on lines and angles with a total of 26 students, with 27% of students completing it and 73. % of students who did not complete. What is the process of developing valid, practical and effective RPP, BA and LKPD tools using the context of tumbur statues by utilizing wingeom as a learning medium on lines and angles? The aim is to determine the level of validity, practicality and effectiveness of RPP, BA and LKPD as learning tools using the context of tumbur and wingeom statues as learning media on lines and angles. This research includes Research and Development research with a 4-D model approach. The development of RPP, BA and LKPD which have been validated by each validator is declared "Valid". The RPP, BA and LKPD developed were declared to meet practicality as the response to the RPP, BA and LKPD was in the "Very Good" category, the implementation of the RPP, BA and LKPD tools in the learning process was in the "Completely Implemented" category. The RPP, BA and LKPD were declared effective, as there were two aspects achieved, namely the effectiveness of the time used in accordance with the design and the student learning outcomes test which achieved classical completeness as many as 19 students and 79.2% were declared complete based on the KKM